2008
DOI: 10.1620/tjem.214.27
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of Body Mass Index Criteria in Obese School-Aged Children

Abstract: Childhood obesity is a medical and social problem in Japan. The number of obese children has been increasing steadily since 1980 according to a survey on school health statistics. However, more simple and reliable criteria for assessment of obesity in children are required. The aim of this study was to establish gender-and age-specifi c body mass index (BMI) cutoff values for evaluation of obesity in school-aged children. A total of 100,587 elementary school, junior and senior high school students, aged 6 to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…In three patients, maintenance therapy with MMF was also continued. In ten patients, RTX infusion for a mean followup period of 17 (range 13-21) months), resulted in a reduction of the mean PSL dose from 0.39±0.18 to 0.15± 0.14 mg/kg per day (63% reduction, p<0.01), the mean 12-month relapse rates from 4.1±1.7 to 0.6±0.6 episodes (86% reduction, p<0.01), and the obesity index, which is defined by the formula: (measured weight -ideal body weight) / ideal body weight × 100% [12] from 8.9±20.5 to 1.9± 12.5% (p<0.05).…”
Section: Resultsmentioning
confidence: 99%
“…In three patients, maintenance therapy with MMF was also continued. In ten patients, RTX infusion for a mean followup period of 17 (range 13-21) months), resulted in a reduction of the mean PSL dose from 0.39±0.18 to 0.15± 0.14 mg/kg per day (63% reduction, p<0.01), the mean 12-month relapse rates from 4.1±1.7 to 0.6±0.6 episodes (86% reduction, p<0.01), and the obesity index, which is defined by the formula: (measured weight -ideal body weight) / ideal body weight × 100% [12] from 8.9±20.5 to 1.9± 12.5% (p<0.05).…”
Section: Resultsmentioning
confidence: 99%
“…1). The mean obesity index was defined by the formula: ðmeasured weight À ideal body weightÞ= ideal body weight  100% [9]. On the other hand, no statistical difference was found in the mean standard deviation (SD) score for height of the patients at final observation in comparison to that at the start of treatment Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible, however, that the use of BMI as a predictor of obesity could result in misclassification of obesity status, particularly for taller children [20]. Although there has been debate regarding the validity of the 95th percentile cutoff point for obesity among children and adolescents [20][21][22][23][24], it has been reported that the Center for Disease Control and Prevention cutoff points for obesity based on BMI, which the current study used, has high sensitivity and specificity for determining obesity even in school-aged children [21,23].…”
Section: Discussionmentioning
confidence: 99%